Cyclic AMP Pathway Suppress Autoimmune Neuroinflammation by Inhibiting Functions of Encephalitogenic CD4 T Cells and Enhancing M2 Macrophage Polarization at the Site of Inflammation - Veremeyko, Tatyana; Yung, Amanda W. Y.; Dukhinova, Marina; Kuznetsova, Inna S.; Pomytkin, Igor; Lyundup, Alexey; Strekalova, Tatyana; Barteneva, Natasha S.; Ponomarev, Eugene D. (Frontiers in Immunology, 2018)
Although it has been demonstrated that cAMP pathway affect both adaptive and innate cell functions, the role of this pathway in the regulation of T-cell mediated central nervous system (CNS) autoimmune inflammation, such as in experimental encephalomyelitis (EAE), remains unclear. It is also unclear how cAMP pathway affect function of CD4 T cells in vivo at the site of inflammation. We found that adenylyl-cyclase activator Forskolin besides inhibition of functions autoimmune CD4 T cells also upregulated miR-124 in the CNS during EAE, which is associated with M2 phenotype of microglia/macrophages. Our study further established that in addition to direct influence of cAMP pathway on CD4 T cells, stimulation of this pathway promoted macrophage polarization towards M2 leading to indirect inhibition of function of T cells in the CNS. We demonstrated that Forskolin together with IL-4 or with Forskolin together with IL-4 and IFNγ effectively stimulated M2 phenotype of macrophages indicating high potency of this pathway in reprograming of macrophage polarization in Th2- and even in Th1/Th2- mixed inflammatory conditions such as EAE. Mechanistically Forskolin and/or IL-4 activated ERK pathway in macrophages resulting in upregulation of M2-associated molecules miR-124, Arg1 and Mrc1, which was reversed by ERK inhibitors. Administration of Forskolin after the onset of EAE substantially upregulated M2 markers Arg1, Mrc1, Fizz1 and Ym1 and inhibited M1 markers NOS2 and CD86 in the CNS during EAE resulting in decrease in macrophage/microglia activation, lymphocyte and CD4 T cell infiltration, and the recovery from the disease. Forskolin inhibited proliferation and IFNγ production by CD4 T cells in the CNS but had rather weak direct effect on proliferation of autoimmune T cells in the periphery and in vitro, suggesting prevalence of indirect effect of Forskolin on differentiation and functions of autoimmune CD4 T cells in vivo. Thus, our data indicate that Forskolin has potency to skew balance towards M2 affecting ERK pathway in macrophages and indirectly inhibit pathogenic CD4 T cells in the CNS leading to suppression of autoimmune inflammation. These data may have also implications for future therapeutic approaches to inhibit autoimmune Th1 cells at the site of tissue inflammation.